2017
DOI: 10.1128/aac.00400-17
|View full text |Cite
|
Sign up to set email alerts
|

The Etest Performed Directly on Blood Culture Bottles Is a Reliable Tool for Detection of Fluconazole-Resistant Candida albicans Isolates

Abstract: We assessed the ability of the Etest performed directly on positive blood cultures (ET DIR ) to detect fluconazole susceptibility in 6 fluconazole-resistant and 12 fluconazole-susceptible Candida albicans isolates, according to CLSI M27-A3 and EUCAST EDef 7.2 procedures. Categorical agreement between ET DIR and broth microdilution was 100% when the trays were incubated at 25°C and trailing effect was ruled out. ET DIR is a reliable procedure when screening for the presence of fluconazole resistance in C. albic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The following tests were performed on isavuconazole nonewildtype isolates to discriminate between trailing or nonsusceptibility: antifungal susceptibility to fluconazole, voriconazole and posaconazole (MilliporeSigma, St Louis, MO, USA); and isavuconazole MICs obtained either by EUCAST but after incubation of trays at 25 C [11] or by Etest (bioM erieux España, Madrid, Spain) performed as recommended by the manufacturer.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…The following tests were performed on isavuconazole nonewildtype isolates to discriminate between trailing or nonsusceptibility: antifungal susceptibility to fluconazole, voriconazole and posaconazole (MilliporeSigma, St Louis, MO, USA); and isavuconazole MICs obtained either by EUCAST but after incubation of trays at 25 C [11] or by Etest (bioM erieux España, Madrid, Spain) performed as recommended by the manufacturer.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
“…In the first study, the Etest was evaluated on blood cultures for the detection of fluconazole resistance in C. albicans. The results showed 100% CA with reference broth microdilution techniques (both CLSI and EUCAST) when trailing was ruled out [106]. In the second study, direct susceptibility by Etest was performed for micafungin and anidulafungin-susceptible and -resistant strains.…”
Section: Etest For Direct Antifungal Susceptibility Testing On Blood mentioning
confidence: 96%
“…The Etest method for direct MIC determination from positive blood culture bottles was evaluated and described below [104][105][106][107][108]. The first evaluation was conducted on 138 positive blood cultures containing yeasts (mainly Candida spp.).…”
Section: Etest For Direct Antifungal Susceptibility Testing On Blood mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular detection of resistance would speed up the results, although to date these techniques are pending on validation for their use with blood samples (5,13). In a previous study, we showed that the Etest directly performed on positive blood cultures (ET DIR ) is a reliable procedure to rapidly detect fluconazole-and echinocandin-resistant isolates (14)(15)(16). Moreover, anidulafungin-containing plates were useful to screen for the presence of echinocandin-resistant C. glabrata isolates directly from positive blood cultures (16).…”
mentioning
confidence: 99%